Legitimacy and empirical evidence in the UK courts. Issue 3 (2nd July 2016) - Blackham, Alysia
ABSTRACT: This article explores how UK courts and tribunals could and do use empirical evidence to build the legitimacy of legal institutions. Drawing on case studies from negligence and discrimination law, it argues that the approach to empirical evidence in the UK courts is largely typified by ad hoc, unprincipled, and unpredictable engagement. Strategies for laying stronger foundations to bridge these apparent disconnections between the courts and society, and for promoting the effective use of empirical evidence in the courts, are explored.